Anxiety Behavior in Pigs (Sus scrofa) Decreases Through Affiliation and May Anticipate Threat - Norscia, Ivan; Collarini, Edoardo; Cordoni, Giada (Frontiers in Veterinary Science, 2021)
Anxiety is a physio-psychological state anticipating an imminent threat. In social mammals it is behaviourally expressed via displacement activities and buffered via affiliation. Anxiety research on domestic pigs (Sus scrofa) has mostly focused on abnormal/stereotypic behaviour associated with intensive farming. We investigated how anxiety is expressed and modulated in semi-free ranging pigs, in natural habitats. Owing to pigs’ socio-cognitive complexity, we posited that displacement activities, if such, would increase after a (stressful) intra-group aggression (Prediction 1), be reduced by affiliation (Prediction 2) and influenced by individual/contextual factors (Prediction 3). From 224 videos recorded on 44 adults (Mean±SD/subject: 4.84 ±1.85hs) at the ‘Ethical Farm Parva Domus’ (Turin, Italy), we extracted possible displacement activities (vacuum-chewing, scratching/body-rubbing, head/body-shaking, and yawning) in fourthree-min conditions: before (BE) and after aggression events, in the absence (AE) or presence (AA) of post-aggression affiliation, and a matched-control (no event; MC). We conducted a minute-by-minute analysis in AE/AA and assessed the effect of subjects’ involvement in a conflict (aggressor, aggression’s recipient, bystander). All activities were higher in AE than in BE condition - thus being anxiety markers - and all of them decreased to baseline levels in AA, faster compared to AE. Hence, anxiety behaviour in pigs was socially buffered. Intriguingly, anxiety behaviour was expressed significantly more by bystanders than opponents, which suggests that pigs may be able to anticipate imminent threats. By highlighting how anxiety is managed under extensive farming, this study contributes to the understanding of pig welfare.